THE CHARACTER ANALYSIS OF ELFRIDE SWANCOURT IN HARDY’S A PAIR OF BLUE EYES NOVEL - Margareta Lughu, Maryam (Yayasan Akrab Pekanbaru, 2021)
The purpose of this study is to analyze the character of Elfride Swancourt especially to reveal the flaws within her character and their influence that has led her to a miserable life. This research is categorized as a qualitative research since the data are in form of words, quotations and statements. The data are collected from the primary source that the novel itself, A Pair of Blue Eyes and the secondary sources are some books and references that support the analysis. In analyzing the data, the objective approach has been used. The result shows that the main character, Elfride Swancourt has a weak personality because she is incapable of improving or even changing the flaws and has not tried to reach her happiness. The main character A Pair of Blue Eyes, Elfride Swancourt has some flaws within her character. She is inexperienced, childish, doubtful and fickle, disloyal, fainthearted and docile. She obeys her father’s will to marry a man who has the same social stratum with them, the high class in accordance with her father’s recommendation. Those flaws have led her life into a tragic life. The Effect of The Flaws to Elfride’s life, she suffers physically and spiritually. She gets harsh treatment from her family and dies five months later after marrying Lord Spenser Hugo Luxellian, a man from high class, same social stratum with her.